Impacts of corrugation profiles on the flow and heat transfer characteristics in trapezoidal corrugated channel using nanofluids - Ajeel Aljebur, Raheem Kadhim; Wan Salim, Wan Saiful-Islam; Hasnan, Khalid (Penerbit Akademia Baru, 2018)
In this paper, turbulent forced convection of nanofluids flow in different configurations of trapezoidal corrugated channels is numerically investigated over Reynolds number ranges of 10000–30000. This study evaluates the effects of four different types of nanofluids which are Al2O3, CuO, SiO2 and ZnO–water under constant heat flux condition (10kw/m2). The governing equations of continuity, momentum and energy are solved using finite volume method (FVM). The study was carried out at 8% volume fraction of nanoparticles with 20nm particle diameters. Simulation results show that the corrugation profile has a significant impact on the thermal performance compare with straight profile. Furthermore, by adopting new channel geometry, the heat transfer enhancement can be improved more than two times that for straight channels. Among the nanofluid evaluated here, SiO2-water offers the highest enhancement of heat transfer. For all studied forms, the nozzle rib configuration of trapezoidal corrugated channel achieved maximum PEC and can lead to more compact heat exchangers.